Creating Sustainable Business Interest Through Innovation in Early Childhood Education - Indrawati Indrawati; Wahira Wahira (Journal of Social Science and Economics (JOSSE), 2024)
This article examines the important role of innovation in early childhood education to foster interest in sustainable business. Facing global economic challenges and rapid social change, early childhood education plays an important role in developing an entrepreneurial spirit that is not only focused on profit, but also sustainability. This research highlights how innovation in service programs, curriculum, teaching methods, and use of technology can encourage educators to create businesses that are environmentally friendly, ethical, and have a positive impact on society. By combining entrepreneurial principles with social and environmental awareness, early childhood education can be a driving force in creating a generation of entrepreneurs with a long-term vision. This article also discusses various early childhood education initiatives that have succeeded in fostering interest in sustainable entrepreneurship among early childhood education managers. In the end, this article provides recommendations that early childhood education must continue to innovate to produce entrepreneurs who are not only financially successful, but also environmentally and socially responsible